Groundwater protection and preservation - Results from a survey to Portuguese farmers - Rebelo, M. (2015)
This report presents a descriptive analysis of the responses to a survey about protection and preservation of groundwater conducted with a sample of Portuguese farmers of the Algarve region. This survey was developed in the context of the project MARSOL – Managed Aquifer Recharge Solutions (European Union Seventh Framework Programme For Research, Technological Development and Demonstration – Grant Agreement nr. 619120).